Mengintegrasikan Computational Thinking (CT) dalam Pemecahan Soal AKM Numerasi di SDN 2 Kutapanjang - Marni Purnama Sari; Sukmawarti Sukmawarti; Hidayat Hidayat (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to analyze the application of the Computational Thinking (CT) approach in solving numeracy Minimum Competency Assessment (AKM) problems in elementary school students. The numeracy AKM measures students' ability to understand and apply mathematical concepts in daily life, which demands high-level thinking skills. The CT approach, which consists of four main components, decomposition, pattern recognition, abstraction, and algorithmic thinking, can assist students in solving these problems in a more systematic way. This study uses a qualitative descriptive method, with subjects consisting of teachers and students in grade V of SDN Kutapanjang. Data was collected through observation, interviews, and analysis of student worksheets. The results of the study show that the application of CT allows students to more easily understand the structure of the questions, develop solving strategies, and improve accuracy in answering numeracy questions. The conclusion of this study is that the integration of Computational Thinking in numeracy learning can improve students' analytical and strategic abilities in dealing with AKM questions, as well as prepare them for future academic challenges.